The impacts of digital divide on e-government usage: A qualitative research - Rahman, Arief; Quaddus, Mohammed; Galbreath, Jeremy (IRM, 2012)
E-government readiness in Indonesia showed no improvement from year to year, indicating that the implementation of e-government is encountering serious problems. Despite the lack of empirical evidence, it is indicated that one of them is digital divide. This research paper aims to validate and examine the tentative research model. This study investigates the impacts of digital divide on e-government usage, particularly on the systems provided by local governments, and to conceptualize ‘innovativeness divide’ in order to understand digital divide more comprehensively. The research used qualitative method by conducting semi-structured interviews with 12 informants and took place in Sleman Regency and Tulungagung Regency of Indonesia. The results show that digital divide is a significant problem in Indonesia, which should be resolved in order to improve the usage of e-government. The research is significant for scholars to give an empirical evidence of digital divide and its impact on e-government systems, especially in the Asian countries. For the local governments, this research may contribute to policy making in improving the e-government readiness.